Changes in physicochemical property and its potential regulatory mechanism for the formation of water core of the Fuji apples post‐harvesting. (18th February 2023) - Wang, Xuanyu; Wang, Rui; Zhuang, Min; Ke, Sheng; Wang, Anqi; Zhou, Zhongkai
Summary: This study analysed the factors for influencing the occurrence of water core in apples and proposed a potential metabolism following its post‐harvesting. By comparing the ordinary pulp and the region within the water core in different post‐harvesting stages of the Fuji apples, although the occurrence of water core did not significantly change the appearance of the apples, its interior firmness decreased with increased cell permeability. Furthermore, fructose content decreased, and sorbitol content increased rapidly accompanied by a reduction of sorbitol dehydrogenase activity at the site of water core. The cell morphology also demonstrated that the cells became denser and the blue aggregates formed. It indicated that the cell walls were saturated with locally highly accumulated sorbitol, followed by visualised transparent spots. In summary, the occurrence of water core during the post‐harvesting of Fuji apples was found to be related to the increased sorbitol content and the corresponding decreased dehydrogenase activity. Abstract : This study analyzed the factors for influencing the occurrence of water‐core in apples, and proposed a potential metabolism following its post‐harvesting. By comparing the ordinary pulp and the region within the water‐core of the Fuji apples, fructose content decreased, and sorbitol content increased rapidly accompanied by a reduction of sorbitol dehydrogenase (SDH) activity at the site of water‐core. The cell morphology also demonstrated the cells became denser and the blue aggregates formed. It indicated that the cell walls were saturated with locally highly accumulated sorbitol, followed by visualized transparent spots. It is speculated that the occurrence of water‐core during the post‐harvesting of Fuji apples was found to be related to the increased sorbitol content and the corresponding decreased dehydrogenase activity.